Foreign Direct Investment and Economic Growth: Empirical Assessment of the Nigerian Economy (1986 – 2019) - Chinedu Maurice Umezurike; Amalachukwu Chijindu Ananwude; Patrick Amaechi Mbanefo (Journal La Bisecoman, 2021)
The purpose of this study is to examine the impact of foreign direct investment on the growth of the Nigerian economy. The Autoregressive Distributive Lag (ARDL) technique was used to analyze data spanning the years 1986 to 2019. The preliminary findings of the ARDL suggested that foreign direct investment and economic development in Nigeria had a long-run link. According to the stated finding, foreign direct investment has a considerable positive link with the rate of real gross domestic product growth. Similarly, total exports are positively correlated with the pace of real gross domestic product growth. On the other hand, total non-oil imports and exchange rates show a considerable negative association with the pace of real GDP growth. The Granger causality test indicated that foreign direct investment inflows into Nigeria had no discernible influence on the growth rate of real gross domestic product throughout the study period. Similarly, the pace of real gross domestic product growth is not greatly impacted by the quantity of total exports, total non-oil imports, or exchange rate fluctuations. This report suggested that trade obstacles be removed, particularly those imposed by customs and port officials. Structural trade-oriented policies should be implemented to stimulate economic growth in Nigeria through increased exports in order to attract additional investors and strengthen the country's output growth rate.